SME Business Models and Competence Changes - Hannele Lampela; Kyllikki Taipale-Erävala; Pia Heilmann (International School for Social and Business Studies, 2017)
As a result of changes in the local or regional business environment, small and medium-sized enterprises (SMEs) in many industries are facing the need to change their business models radically and seize new business opportunities or fall out of business. Although the important impact of SMEs in economic growth and job creation is well known, current knowledge is rather limited on the effects of competences for changing the business models in SMEs. This paper focuses on the links between SME competence changes and business model innovations in industrial structural changes in the external environment. The findings of a comparative case study of Russian and Finnish SMEs identified the positive attitude to change and activeness in external networking and in seeking new opportunities as enabling competences for business model innovation. The practical implications highlight the competence transformation strategies enabling business model innovation and the effects of different institutional environments.